ANXIETY IN DENTISTRY - Lahoud Salem, Victor (2004)
Anxiety is an emotional state where it could be experienced a permanent anguish and desperation because of unknown reasons at consciousness level. It could affect people without any age distinction overall those people with constant family o work stress including also everyone with deep behaviour patrons related to perfection in what they do or sayo It is a constant desperation where someone does not Uve or enjoy the present moments and it is always thinking in the nearest coming activity. Unjustified and overreacting emotion which is characterized by hip recitation activity (chest oppression,attention disorders, trembling, increasing heartbeats) Anxiety is apprehension-feeling stress responding to threat. It is considered normal when is a temporal condition during a stressing or untrue situation. Intense inappropriate and long periods of anxiety could be a sign of anxiety disorder.